Important historical, social, political and economic Arabela population - Buenaño Olivo, Julio C. (2011)
The population Arabela part of many peoples of the Peruvian Amazon. Since neo-liberal policies imposed as state policies to encourage foreign private investment and national, have been affecting the territories of the various peoples of our Amazon. Because of this, ecological and social impacts are very negative, economically and culturally disturbing people Arabella, who was first contacted in 1945. For some time this part has been speculation over the territory they currently occupy, emerging views that support the existence of Aboriginal peoples in voluntary isolation. The present work is the product of an expedition involving in situ to determine such claims.